MANIFESTATIONS OF THE LIVING QUR’AN IN MALAYSIA: THE INTERACTION BETWEEN THE SACRED TEXT AND MALAY CULTURE - Farwah bin Ahmad Fahmi (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2026)
The Living Qur’an approach has emerged as an important perspective in contemporary Qur’anic studies by positioning the Qur’an not merely as a normative text but as a lived social reality manifested in the religious practices, traditions, and cultural experiences of Muslim communities. In Malaysia, the interaction between the Qur’an and Malay culture has shaped distinctive patterns of religiosity and played a significant role in the construction of Malay-Muslim identity. However, scholarly attention to the role of the Living Qur’an in identity formation and its negotiation with contemporary social transformation remains limited. This study aims to analyze the manifestations of the Living Qur’an within Malaysian Malay society, particularly in socio-religious rituals, the internalization of Qur’anic values, and the construction of Malay-Islamic cultural identity. Employing a qualitative-descriptive approach that combines library research and field observations, this study draws upon the perspectives of Living Qur’an studies, cultural anthropology, and the sociology of religion. The findings reveal that the Qur’an is deeply embedded in Malay social life through various religious and cultural practices, including the recitation of Sūrah Yāsīn, tahlil, marhaban, Qur’anic educational traditions, the use of Jawi script, and diverse Malay-Islamic customary rituals. These practices function not only as expressions of religiosity but also as mechanisms for transmitting values, strengthening social cohesion, and constructing collective Malay-Muslim identity. Furthermore, the study demonstrates that Living Qur’an practices in Malaysia are characterized by a dynamic dialectical process involving the sacred text, Malay customs, religious authority, and contemporary social transformation shaped by modernization and digital media. The findings underscore the role of the Qur’an as a symbolic and cultural resource continuously reproduced in Malay society, serving as a crucial foundation for sustaining Islamic identity amid ongoing social change.